2018
DOI: 10.1007/978-1-4939-8609-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Plasticity at the Mitral and Tufted Cell to Granule Cell Synapse of the Olfactory Bulb Investigated with a Custom Multielectrode in Acute Brain Slice Preparations

Abstract: Single extracellular stimulation electrodes are a widespread means to locally activate synaptic inputs in acute brain slices. Here we describe the fabrication and application of a multielectrode stimulator that was developed for conditions under which independent stimulation of several nearby sites is desirable. For the construction of the multielectrode we have developed a method by which electrode wires can be spaced at minimal distances of 100 μm. This configuration increases the efficiency of stimulation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Assumption 4: The Granule Cells-Mediated Anatomical Connectivity Between Individual Glomerular Ensembles Is Spatially Isotropic While detailed anatomical data on this issue are not available as of yet (since their quantification would require large-scale electron microscopy and reconstruction), currently available evidence indicates that dedicated dendrodendritic connections between certain glomeruli seem unlikely to play a major role in MC-GC connectivity: MCs and yet more so glomerular MC ensembles have radially symmetric dendritic fields as described above, probably to maximize the spatial range of the glomerular input/output. Using a multi-electrode stimulation device, we also consistently observed that a given GC can be excited (and even fired) from several adjacent glomeruli both in rats and mice (Stroh et al, 2012;Chatterjee et al, 2016;Lukas et al, 2018), in line with results based on optogenetic activation (Burton and Urban, 2015). Thus, a given GC is likely to belong to more than one glomerular column, again arguing against specific connectivities.…”
Section: Assumption 3: the Synaptic Density Profile Of Mitral Cells A...supporting
confidence: 83%
“…Assumption 4: The Granule Cells-Mediated Anatomical Connectivity Between Individual Glomerular Ensembles Is Spatially Isotropic While detailed anatomical data on this issue are not available as of yet (since their quantification would require large-scale electron microscopy and reconstruction), currently available evidence indicates that dedicated dendrodendritic connections between certain glomeruli seem unlikely to play a major role in MC-GC connectivity: MCs and yet more so glomerular MC ensembles have radially symmetric dendritic fields as described above, probably to maximize the spatial range of the glomerular input/output. Using a multi-electrode stimulation device, we also consistently observed that a given GC can be excited (and even fired) from several adjacent glomeruli both in rats and mice (Stroh et al, 2012;Chatterjee et al, 2016;Lukas et al, 2018), in line with results based on optogenetic activation (Burton and Urban, 2015). Thus, a given GC is likely to belong to more than one glomerular column, again arguing against specific connectivities.…”
Section: Assumption 3: the Synaptic Density Profile Of Mitral Cells A...supporting
confidence: 83%